PENGARUH FOREIGN OWNERSHIP, LEVERAGE, CAPITAL INTENSITY, DAN PROFITABILITAS TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2022-2025 - Annisya Fauziah Audila; Arif; Julia Dwi Nuritha Siregar; Indra Pahala (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2026)
This study aims to examine the effect of Foreign Ownership, Leverage, Capital Intensity, and profitability on Tax Avoidance in manufacturing companies listed on the Indonesia Stock Exchange during the 2022–2025 period. The study employed a quantitative approach using secondary data obtained from annual reports and financial statements. The sample was selected using purposive sampling, resulting in 120 observations. Tax Avoidance was proxied by the Effective Tax Rate (ETR), and the data were analyzed using panel data regression with EViews software. The results indicate that Leverage and profitability affect Tax Avoidance, whereas Foreign Ownership and Capital Intensity do not affect Tax Avoidance. These findings suggest that Tax Avoidance practices in manufacturing companies are more strongly influenced by firms’ financial characteristics than by Foreign Ownership structure and the level of investment in fixed assets.